Perceived intrinsic, social, and environmental barriers for weight management in older Hispanic/Latino adults with obesity. (31st August 2022) - Dao, Maria Carlota; Yu, Zihan; Maafs‐Rodríguez, Ana; Moser, Brandy; Cuevas, Adolfo G.; Economos, Christina D.; Roberts, Susan B.
Abstract: Background: The burden of obesity and chronic disease is increasing in the older US Hispanic/Latino adult population. There is limited evidence on successful weight management strategies as perceived by this population. Assessing barriers and opportunities for weight management using mixed methods is a robust approach to collect in‐depth information that can be applied to the development of well‐tailored weight management interventions for this population. Objective: The objective of this study was to assess perceived individual, interpersonal, and environmental factors that influence weight management in older Hispanic/Latino adults. Methods: This community‐based cross‐sectional study included 23 Hispanic/Latino older (>50y) adults with obesity (BMI >30 kg/m 2 ). Perceived barriers and opportunities for weight management were assessed through validated questionnaires and focus groups. Prospectively registered on ClinicalTrials.gov (NCT03978416) on 7 June 2019. Results: In this demographically heterogeneous population, language acculturation was generally low, and the frequency of poor dietary behaviors was high. Participants linked financial strain to lower diet quality, as well as anxiety to uncontrolled eating and food cravings. Social support and trust in healthcare professionals were perceived as priorities for healthy eating. Structural and environmental barriers such as affordability and availability of culturally preferred foods were also identified as influences on food choices and eating behavior. Conclusions: This study revealed opportunities for culturally tailored weight management interventions in older Hispanic/Latino adults with obesity. Clinical Trial Registry Number: NCT03978416 (ClinicalTrials.gov )